Evaluation of elevated heart rate as a sympathetic nervous system biomarker in essential hypertension. Issue 8 (August 2020) - Esler, Murray; Lambert, Gavin; Esler, Danielle; Ika Sari, Carolina; Guo, Ling; Jennings, Garry
Abstract : Background: There is a need for an easily accessible biomarker of sympathetic nervous activation in essential hypertension, but none exists. Heart rate (HR) has been suggested, but requires validation, now doubly important as an elevated HR in hypertension has emerged as an independent cardiovascular risk factor. Methods: Isotope dilution methodology was used to measure total and regional noradrenaline spillover and adrenaline secretion rates in 30 patients with unmedicated essential hypertension and in a comparator group of 48 healthy participants with normal blood pressure. The particular interest was in the relationship of measured HR to cardiac noradrenaline spillover, the measure of cardiac sympathetic activity. Results: Sympathetic activation was present in the patients with essential hypertension, evident in significantly increased mean cardiac, renal and total noradrenaline spillover rates. Adrenaline secretion was normal. HR in hypertension correlated directly with cardiac noradrenaline spillover ( r = 0.82, P = 9.3 × 10 –5 ), but not with renal noradrenaline spillover or adrenaline secretion. 67% of the variance in HR was attributable to differences in cardiac sympathetic activity. Among hypertensive patients there was no internal correlation between cardiac noradrenaline spillover, renal noradrenaline spillover and adrenaline secretion; the sympathetic activation commonly was not 'global'. In healthy participants HR did not correlate with measures of sympathetic activity or adrenaline secretion. Conclusion: When sympathetic activation exists in essential hypertension it is differentiated, not necessarily involving all sympathetic outflows. An elevated HR proved to be a biomarker of cardiac sympathetic activation but not activation of the renal sympathetic outflow. Identifying activation of the cardiac sympathetic outflow as the prime mechanism of hypertension tachycardia is relevant to therapies which should now be considered to minimize cardiovascular risk in this clinical setting. Is an elevated HR a valid biomarker of sympathetic activation in essential hypertension? Yes, but only for the cardiac sympathetic outflow. The unavoidable principle is that regional differentiation of sympathetic responses in essential hypertension means that no simple test can ever represent each and every sympathetic outflow.